2006
DOI: 10.1074/jbc.m601805200
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Decay-accelerating Factor as a Receptor for Helicobacter pylori and a Mediator of Gastric Inflammation

Abstract: Persistent gastritis induced by Helicobacter pylori is the strongest known risk factor for peptic ulcer disease and distal gastric adenocarcinoma, a process for which adherence of H. pylori to gastric epithelial cells is critical. Decay-accelerating factor (DAF), a protein that protects epithelial cells from complement-mediated lysis, also functions as a receptor for several microbial pathogens. In this study, we investigated whether H. pylori utilizes DAF as a receptor and the role of DAF within H. pylori-inf… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
37
0

Year Published

2008
2008
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(38 citation statements)
references
References 50 publications
(52 reference statements)
1
37
0
Order By: Relevance
“…This in turn may induce the transcription of a novel subset of proinflammatory genes that are exclusively activated in an AP-1-dependent manner during H. pylori infection. One example of this is the decay-accelerating factor (DAF), a H. pylori cellular receptor previously shown to be upregulated following contact with H. pylori (85). Although the DAF promoter contains a B response element, it was found that DAF expression in response to H. pylori was dependent on p38 phosphorylation and totally independent of NF-B (86 -89).…”
Section: Discussionmentioning
confidence: 99%
“…This in turn may induce the transcription of a novel subset of proinflammatory genes that are exclusively activated in an AP-1-dependent manner during H. pylori infection. One example of this is the decay-accelerating factor (DAF), a H. pylori cellular receptor previously shown to be upregulated following contact with H. pylori (85). Although the DAF promoter contains a B response element, it was found that DAF expression in response to H. pylori was dependent on p38 phosphorylation and totally independent of NF-B (86 -89).…”
Section: Discussionmentioning
confidence: 99%
“…Bacterial Strains-Experiments were performed with the H. pylori cag ϩ strains J166 and 7.13 (13,29). Isogenic cagA, cagE, and cagM null mutants were constructed by insertional mutagenesis using aphA (conferring kanamycin resistance) as previously described (30,31) and were selected on Brucella agar with kanamycin (25 g/ml).…”
Section: Methodsmentioning
confidence: 99%
“…Level-We previously demonstrated that H. pylori upregulates DAF in vitro (13). To determine whether DAF induction was transcriptionally or post-transcriptionally mediated, the H. pylori cag ϩ strain J166 was co-cultured with MKN28 gastric epithelial cells that had been pretreated with either actinomycin D (inhibitor of transcription) or cycloheximide (inhibitor of translation).…”
Section: H Pylori Induction Of Daf Is Regulated At the Transcriptionalmentioning
confidence: 99%
See 2 more Smart Citations